PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL DAN FINANCIAL DISTRESS PADA AUDIT REPORT LAG - Khansa Aulia Bara, (2023)
This research is using quantitative study that aims to ensure empirically the influence of firm size, institutional ownership and financial distress on audit report lag. The population in this study are transportation and logistics companies that have been listed on the Indonesia Stock Exchange in the 2019-2021 period. The samples in this study were taken using the purposive sampling method, so that 72 samples were obtained from 93 companies populations. The data used in this study is secondary data taken from the financial reports. Hypthotesis was being tested using Multiple Linear Regression Analysis using the STATA 17. The results of this study indicates that financial distress has a significant and negative effect on audit report lag, while the firm size and institutional ownership have no effect on audit report lag.